1999
DOI: 10.1038/sj.onc.1202613
|View full text |Cite
|
Sign up to set email alerts
|

SSX and the synovial-sarcoma-specific chimaeric protein SYT-SSX co-localize with the human Polycomb group complex

Abstract: Chromosome translocation t(X;18)(p11.2;q11.2) is unique to synovial sarcomas and results in an`in frame' fusion of the SYT gene with the SSX1 or closely-related SSX2 gene. Wild-type SYT and SSX proteins, and the SYT-SSX chimaeric proteins, can modulate transcription in gene reporter assays. To help elucidate the role of these proteins in cell function and neoplasia we have performed immunolabelling experiments to determine their subcellular localization in three cell types. Transient expression of epitope-tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 32 publications
4
84
0
Order By: Relevance
“…Hence, efforts have been made to understand the molecular basis of synovial sarcoma, but the origin tissue of synovial sarcoma is still not clarified. A SYT-SSX fusion gene, a product of chromosomal translocation t(X;18)(p11;q11), is a wellknown feature of synovial sarcoma and it is considered to play a critical role in the oncogenesis of synovial sarcoma (Turc-Carel et al, 1986;Clark et al, 1994;Brett et al, 1997;Lim et al, 1998;Soulez et al, 1999). Furthermore, several groups reported the gene expression profile analysis using cDNA microarray and revealed that synovial sarcoma showed a distinct gene expression pattern compared with other spindle cell sarcomas (Nagayama et al, 2002;Nielsen et al, 2002;Segal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, efforts have been made to understand the molecular basis of synovial sarcoma, but the origin tissue of synovial sarcoma is still not clarified. A SYT-SSX fusion gene, a product of chromosomal translocation t(X;18)(p11;q11), is a wellknown feature of synovial sarcoma and it is considered to play a critical role in the oncogenesis of synovial sarcoma (Turc-Carel et al, 1986;Clark et al, 1994;Brett et al, 1997;Lim et al, 1998;Soulez et al, 1999). Furthermore, several groups reported the gene expression profile analysis using cDNA microarray and revealed that synovial sarcoma showed a distinct gene expression pattern compared with other spindle cell sarcomas (Nagayama et al, 2002;Nielsen et al, 2002;Segal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, several findings afford a role of the CTA SSX in stem cell biology. SSX is recruited to the nuclear domains occupied by the PcG protein Bmi-1 [44], a regulator of stem cell self-renewal [45]. SSX is involved in mesenchymal-to-epithelial transition (MET) by promoting matrix metalloproteinase 2 expression and changing E-cadherin levels, consequently affecting cell migration [28].…”
Section: Ctas and Stem Cell Developmentmentioning
confidence: 99%
“…10,11,15 The N-terminus of SYT determines its nuclear localization and the 34 amino acids of C-terminus (also called SSXRD domain) mediates SSX nuclear localization. The SSXRD domain also plays a pivotal role in determining the subnuclear localization of the SYT-SSX chimeric oncoprotein.…”
Section: Discussionmentioning
confidence: 99%